The Convergence of Management Accounting and Human Resource Management: A Systematic Literature Review - Rizalnur Firdaus; Lila Widya Rahajeng; Tasnim Nikmatullah Realita; Moh Amin Rosidi (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2026)
This study aims to analyze the convergence between Environmental Management Accounting (EMA), Human Resource Management (HRM), and sustainability using a Systematic Literature Review (SLR) approach. The study adopts the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to ensure a systematic, transparent, and replicable literature selection process. Data were collected from Google Scholar and SciSpace databases within the 2020 – 2026 period using Boolean-based keyword combinations. The selection process resulted in 15 articles that met the inclusion criteria for further analysis. The data were analyzed using thematic analysis to identify research patterns, relationships, and gaps related to the integration of EMA, HRM, and organizational sustainability. The findings indicate that EMA serves as a strategic information system for managing environmental costs, while HRM, particularly through Green Human Resource Management (GHRM) practices acts as a driver of employees’ pro-environmental behavior. The convergence of these two aspects contributes significantly to enhancing organizational sustainability performance in a holistic manner. This study contributes to strengthening the integration of system-based and human-centered perspectives in sustainability and provides practical implications for organizations in developing environmentally oriented strategies.